Pemanfaatan Teknologi Virtual Reality untuk Media Informasi Sekolah SMK Negeri 01 Boalemo - Afiq Fandra Abdulrahman; Dian Novian; Manda Rohandi; Arif Dwinanto; Moh. Hidayat Koniyo; Abd. Aziz Bouty; Alfian Zakaria (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
The development of digital technology has encouraged innovation in information delivery in the field of education, one of which is through the utilization of Virtual Reality (VR). This study aims to develop a VR-based information media as a means of introducing the environment and facilities of SMK Negeri 1 Boalemo and to analyze users’ responses to the developed media. The method used in this research is the Multimedia Development Life Cycle (MDLC), which consists of the stages of concept, design, material collecting, assembly, testing, and distribution. Data were collected through observation, documentation, and questionnaires involving 15 students as respondents. The results showed that the developed VR application was able to present the school environment in the form of interactive and immersive 3D visuals. Testing on various devices indicated that the application operated optimally on smartphones with a minimum specification of 6 GB RAM and gyroscope sensor support. The questionnaire results revealed that the majority of respondents gave ratings in the “very good” category with a percentage of 87%, particularly in aspects of appearance, ease of use, clarity of information, and level of attractiveness. Therefore, the developed VR-based information media is considered effective and feasible to be used as a supporting tool in introducing the school environment and enhancing a more engaging and interactive learning experience.